2018
DOI: 10.1080/0907676x.2018.1473452
|View full text |Cite
|
Sign up to set email alerts
|

Unintended consequences of translation technologies: from project managers’ perspectives

Abstract: Acknowledgments I would like to extend my gratitude to the study participants for taking time out of their busy schedules to share their insights. This study was conducted as part of the larger project, When Translation Meets Technologies: Language Service Providers (LSPs) in the Digital Age, funded by the University of Portsmouth. Bio note Akiko Sakamoto is senior lecturer in translation studies and Japanese language at the University of Portsmouth, UK. She holds a PhD in translation studies from the Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 18 publications
(7 reference statements)
0
4
0
1
Order By: Relevance
“…In other words, the technical and cognitive effort levels are not taken into account in this measure, and this could Quaderns de Filologia: Estudis Lingüístics XXVII: 17-48. doi: 10.7203/QF.27.24622 result in the amount eligible for payment being less than the actual amount of effort to perform the task. The automation of these processes, either of the translation process itself through MTPE, or of the calculation of the editing percentage to adapt the payment, or both at the same time, is causing some translation stakeholders to reject the use of technologies (Sakamoto, 2019). We have also recently seen statements from national and international organisations of professional translators denouncing the use of machine translation in translation processes, such as that of the Association of Audiovisual Translators of Spain 4 .…”
Section: Decrease Of Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the technical and cognitive effort levels are not taken into account in this measure, and this could Quaderns de Filologia: Estudis Lingüístics XXVII: 17-48. doi: 10.7203/QF.27.24622 result in the amount eligible for payment being less than the actual amount of effort to perform the task. The automation of these processes, either of the translation process itself through MTPE, or of the calculation of the editing percentage to adapt the payment, or both at the same time, is causing some translation stakeholders to reject the use of technologies (Sakamoto, 2019). We have also recently seen statements from national and international organisations of professional translators denouncing the use of machine translation in translation processes, such as that of the Association of Audiovisual Translators of Spain 4 .…”
Section: Decrease Of Ratesmentioning
confidence: 99%
“…The effects of digitalization and automation in the language services world are noticeable and substantial, often leading to increased austerity, growing pressures to deliver projects as quickly as possible, and worsening conditions (Moorkens, 2017;Fırat, 2021;Pym & Torres-Simón, 2021). It is clear that technology has created a major disruption in the market, as evidenced by new workflows and the various studies mentioned above (Sakamoto, 2019). However, we consider that every change also offers room for opportunities, and technologies should not always be demonised because they may offer new professional prospects (do Carmo, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Algoritmivälitteinen lähestymis tapa ja tiedon epäsymmetria häiritsevät näistä seikoista neuvottelua sekä tehtävään sopivimman kääntäjän ja mielekkäiden välineiden valintaa. (Artegiani 2021;Sakamoto 2018Sakamoto , 2019 Kääntämisen dematerialisoituminen teknologia välitteisissä prosesseissa ja mielikuvat mekaanisesta toiminnasta saattavat heikentää kääntämisen arvostusta ja tehdä ihmiset entistä haluttomammiksi maksamaan käännöstyöstä (Cronin 2013, 135;Doherty 2016, 963). Narratiiveilla ja käsityksillä on siis konkreettisia käytännön vaikutuksia.…”
Section: Heteromaation Narratiivit Ja Käsitys Kääntämisestäunclassified
“…25-27), MT was not the focus of the interviews, in which the management perspective was represented by a single project manager. Another case in point is Sakamoto, Rodríguez, Berthaud, and Evans's (2017) analysis of focus-group interviews involving project managers in the UK (see also Sakamoto, 2019). Sakamoto et al found that project managers do not always have access to information on how and how much translators may be using MT.…”
Section: Previous Research On Attitudes To Mtmentioning
confidence: 99%